Re-rigging a flagship : the Mexican Government’s CONACYT scholarship programmes and the contested worth of sponsored international student mobility - Saling, Kieve Stone ; 0000-0003-1238-9589 (Policy Reviews in Higher Education, 2025)
This article examines the Mexican government’s recently curtailed CONACYT international scholarships and its sponsored masters’ students who studied in Sweden between 2013 and 2020. It contrasts CONACYT’s human capital theory-based justifications with the experiences of ten sponsored alumni and indicators covering eighty-five such alumni from major Swedish universities. Employing a framework from the economics and sociology of conventions, it highlights institutional stability challenges involving scholarships amidst varying conceptions of worth and changing societal conventions. Findings show that participants express the value of their education and view possibilities for ‘giving back’ in ways that clearly differ from CONACYT’s stated aims–and in ways that do not depend upon physical return. Further analysis indicates under 20% of this group of alumni has returned to Mexico. Non-return had been a widely acknowledged but under-enumerated and nebulous issue which CONACYT previously dismissed. Recent research firmly establishes non-return as a significant fact. This study complements such findings, and using a novel framework, demarcates incoherence, tensions and criticism of CONACYT’s rationales in relation to the institution of ‘scholarships’ in Mexico. It thereby provides insights into CONACYT’s recent radical reform and identifies potential snares for programmes using similar rationale.
Publisher Copyright: © 2025 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: education for development; international student mobility; Mexico; scholarships; Sponsored students